Cecal dilatation and distension in a Holstein calf - Alves, Bárbara de Andrade; Mendonça, Carla Lopes de; Afonso, José Augusto Bastos; Gonçalves, Eldo; Colares, Raquel Ribeiro; Lima, Thatyane Carla de; Arenales, Alexandre (Brazilian Journal of Veterinary Pathology, 2021)
Cecal dilatation and distention is an important disorder in early lactation dairy cows, however, reports describing the anatomical pathology findings of this condition are scarce in the literature. Etiopathogenesis of cecal dilatation and distention is often attributed to high concentrate feeds, but there is also evidence of myoelectrical dysfunction contributing to its occurrence. Diagnosis is often made based on physical exam findings, with the contribution of ancillary exams. This paper aims to describe a case of cecal dilatation with clinical, laboratorial and pathology findings of a 5-month-old Holstein calf that presented abdominal distension, positive succussion of the right flank and mild dehydration. Clinical pathology findings included neutrophilic leukocytosis with regenerative left shift and elevated ruminal chloride. Ultrasonographic examination of the right abdomen showed distended and hypomotile intestinal loops. Despite that, due to the patient’s age, which prevented rectal palpation, and lack of some characteristic clinical and clinical pathology findings, diagnosis was only possible post mortem. Macroscopical and microscopical findings demonstrated cecum dilatation with edema, hemorrhage and thrombi. Despite being well known by large animal clinics, anatomical pathologists must be aware of this condition.